Alcohol and cannabis co‐use and longitudinal gray matter volumetric changes in early and late adolescence. (12th July 2022) - Luo, Xi; Yang, James J.; Buu, Anne; Trucco, Elisa M.; Li, Chiang‐Shan R.
Abstract: Background: Previous studies have characterized the impact of substance use on cerebral structure and function in adolescents. Yet, the great majority of prior studies employed a small sample, presented cross‐sectional findings, and omitted potential sex differences. Methods: Using data based on 724 adolescents (370 females) curated from the NCANDA study, we investigated how gray matter volumes (GMVs) decline longitudinally as a result of alcohol and cannabis use. The impacts of alcohol and cannabis co‐use and how these vary across assigned sex at birth and age were examined. Brain imaging data comprised the GMVs of 34 regions of interest and the results were evaluated with a Bonferroni correction. Results: Mixed‐effects modeling showed faster volumetric declines in the caudal middle frontal cortex, fusiform, inferior frontal, superior temporal (STG), and supramarginal (SMG) gyri, at −0.046 to −0.138 cm 3 /year in individuals with prior‐year alcohol and cannabis co‐use, but not those engaged in alcohol or cannabis use only. These findings cannot be explained by more severe alcohol use among co‐users. Further, alcohol and cannabis co‐use in early versus late adolescence predicted faster volumetric decline in the STG and SMG across assigned sex at birth. Conclusions: Findings highlight the longitudinal impact of alcohol and cannabis co‐use on brain development, especially among youth reporting early adolescent onset of use. The volumetric decline was noted in cortical regions in support of attention, memory, executive control, and social cognition, suggesting the pervasive effect of alcohol and cannabis co‐use on brain development. Abstract : Mixed‐effects modeling showed faster volumetric declines in the caudal middle frontal cortex, fusiform, inferior frontal, superior temporal (STG), and supramarginal (SMG) gyri, at −0.046 to −0.138 cm3/year in individuals with prior‐year alcohol and cannabis co‐use, but not those engaged in alcohol or cannabis use only. These findings cannot be explained by more severe alcohol use among co‐users. Further, alcohol and cannabis co‐use in early versus late adolescence predicted a faster volumetric decline in the STG and SMG across biological sex.